SOCIALIZATION OF YOUTH AND SOCIAL NETWORKS - A. Abdullazizov (Bright Mind Publishing, 2025)
This article is an attempt to show the role, positive and negative consequences of social networks in the daily life of adolescents.
Keywords: Social networks, teenagers, Facebook, Instagram, Vkontakte, worldview, ethics and education, videos, films, books.